Homegardens (Aal-oos-gad) of the Basket People of Southwestern Ethiopia: Sustainable agro-ecosystems characterizing a traditional landscape - Woldeyes, Feleke; Asfaw, Zemede; Demissew, Sebsebe; Roussel, Bernard (Ethnobotany Research and Applications, 2016)
Traditional agricultural landscapes support substantial levels of biological and cultural diversity. Tropical homegardens, which represent sustainable agro-ecosystems, are important components of such landscapes. In this study, homegardens of Basketo Special Woreda of Southwestern Ethiopia have been investigated. The study aims at understanding organization of homegardens, their role in maintenance of biological diversity and also the impact of ongoing changes on the composition and function of the gardens. A total of 60 homegardens (households) were sampled from 12 k’ebele (the smallest administrative unit) selected by employing a combination of purposive and stratified sampling methods. In the study, issues that pertain to local resource perception, management, and use norms as well as plant diversity of the different land-use systems in the landscape are addressed. A total of 207 species, of which 149 are maintained in the homegardens, were recorded from the managed landscape. Biodiversity has been cultivated in these farming units as a result of the farmers’ innate perception of biodiversity value and also due to the characteristic organization of the gardens which promote concentration of plant species. Currently, Basketo homegardens are undergoing unusual dynamics mainly due to market-driven factors. Some crops such as coffee/buna (Coffea arabica L.), which bring better economic return, are expanding and displacing enset/uuts (Ensete ventricosum (Welw.) Cheeseman) (which traditionally forms the basic element of the garden) and other long-existed crops. Drastic alteration of these crop production units could lead to unwanted impacts including a serious deterioration of biological diversity and loss of the sustainability feature of the agro-ecosystems.